A consistent balanced force refined moment-of-fluid method for surface tension dominant two-phase flows. (3rd July 2018) - Zinjala, H. K.; Banerjee, J.
Abstract: Inconsistent implementation of surface tension in an interfacial solver for incompressible two-phase flow results in spurious currents near the interface. The balanced force algorithm (BFA) enforces consistent implementation of surface tension force and pressure gradient at the cell faces thereby generating conservative face center velocity field, even though the cell center velocity may not be divergence free and spurious current free. The implication of this inconsistency is directly reflected in interface smoothness while using a Lagrangian–Eulerian interface evolution in contrary to Eulerian advection where divergence free face velocities are used. This paper describes a consistent balanced force algorithm (CBFA) in collocated grid for consistent implementation of surface tension force. The interface evolution is tracked by refined moment-of-fluid (RMOF) method using Lagrangian–Eulerian advection scheme. In CBFA, additional Poisson equation is solved to obtain cell face corrections for conservative cell center velocity computation. The effectiveness of the proposed method is demonstrated in this article for several test cases.